ANALISIS POSITIONING DESTINASI WISATA DI JAKARTA - Putri Mihsanah Allyusdar; Nanda Fadhli Dzil Ikram Nasution; Satya AJi Wicaksono (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this research is to analyze the attributes, positioning, and market strategy in tourist destinations in Jakarta (Ancol Dreamland, Taman Mini Indonesia Indah, and Ragunan Wildlife Park). Purposive sampling was used to collect the data, and a sample of 51 participants completed online questionnaires (Google forms) that were sent via Instagram. The unit of analysis used in this study were individuals who had visited Ancol Dreamland, Taman Mini Indonesia Indah, and Ragunan Wildlife Park. The method of data analysis in this study used discriminant analysis using SPSS ver 25 software. This study used cross-sectional time dimensions. This means that data is collected only once in a predetermined period of time for the purpose of answering research questions. With the analytical tool used, namely discriminant, it can be concluded that the attributes considered important by consumers are Destination Image and Accessibility, with the marketing strategy used, it can be said that Ancol Dreamland Park can be considered as a market leader.